Case report: Covered stent placement to treat delayed aneurysmal rupture after flow diverter-assisted coil embolization - Chen, Xiheng; Gui, Siming; Dong, Linggen; Zhang, Longhui; Ge, Huijian; Liu, Peng; Li, Youxiang; Lv, Ming (Frontiers in Neurology, 2022)
Introduction Flow diverter (FD) placement is widely accepted as a treatment for large saccular intracranial aneurysms. Delayed aneurysmal rupture (DAR) after FD placement is potentially catastrophic and difficult to treat. To our knowledge, using a Willis covered stent (WCS) to treat DAR after placement of a Pipeline Flex embolization device (PFED) combined with coiling has not been previously reported. Case presentation A 49-year-old woman with an incidental asymptomatic large right supraclinoid internal carotid artery aneurysm was treated with PFED placement and adjunctive coiling. DAR causing subarachnoid hemorrhage occurred 11 hours after the procedure. Treatment using a WCS was successful and resulted in a favorable clinical outcome (modified Rankin scale score 2). Conclusion DAR after FD implantation requires isolation of the aneurysm from the cerebral circulation as soon as possible. WCS placement can achieve this immediately and occlude the aneurysm. We hope our case could provide new idea for similar cases in the future.